COMPARATIVE ANALYSIS OF ECONOMIC EFFICIENCY IN PUBLIC AND PRIVATE SECTOR MANAGEMENT (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This paper presents a comparative analysis of the economic efficiency of management in the public and private sectors. The study examines the distinctive characteristics of management systems in both sectors, their decision-making processes, and the efficiency of resource utilization. Furthermore, the impact of different management approaches on economic outcomes is analyzed, highlighting their respective advantages and limitations. The findings of this research provide a basis for developing practical recommendations to enhance management mechanisms and improve the operational effectiveness of both public and private sector organizations.